The relationships between perfectionism, angry reactions, and antisocial behavior in team sport - Grugan, M. C.; Jowett, G. E.; Mallinson-Howard, S. H.; Hall, H. K. (Sport, Exercise, and Performance Psychology, 2020)
Perfectionism involves extreme requirements for perfection that may give rise to antisocial behavior in team sport. To test this possibility, we first examined pathways linking self-oriented perfectionism and socially prescribed perfectionism to antisocial behavior. We then examined pathways linking other-oriented perfectionism to antisocial behavior via angry reactions to poor teammate performance. A cross-sectional design was used. Competitive team sport athletes (n = 257, Mage = 20.71 years, s = 4.10) completed measures of perfectionism, angry reactions to poor teammate performance, and antisocial behavior. In testing the first aim, we found that self-oriented perfectionism shared no relationship with antisocial teammate behavior and a negative relationship with antisocial opponent behavior. By contrast, socially prescribed perfectionism shared positive relationships with antisocial behavior toward teammates and opponents. In testing the second aim, we found that other-oriented perfectionism shared positive indirect relationships with antisocial behavior toward teammates and opponents via angry reactions to poor teammate performance. In line with recent theoretical assertions, these findings suggest that there may be a darker side to perfectionism that is related to antisocial behavior in team sport.